Guidelines for genetic skeletal dysplasias for pediatricians - Sung Yoon Cho; Dong-Kyu Jin (Korean Society of Pediatric Endocrinology, 2015)
Skeletal dysplasia (SD) is a kind of heterogeneous genetic disorder characterized by abnormal growth, development, differentiation, and maintenance of the bone and cartilage. The patients with SD most likely to be seen by a pediatrician or orthopedic surgeon are those who present with short stature in childhood. Because each category has so many diseases, classification is important to understand SD better. In order to diagnose a SD accurately, clinical and radiographic findings should be evaluated in detail. In addition, genetic diagnosis of SD is important because there are so various SDs with complex phenotypes. To reach an exact diagnosis of SDs, cooperative approach by a clinician, a radiologist and a geneticist is important. This review aims to provide an outline of the diagnostic approach for children with disproportional short stature.